(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2022)
One of the most common reasons for irreversible blindness of people in the Western World is age-related macular degeneration (AMD). Yet, there is no possiblity to cure this degenerative disease. Promising resarch is based on human induced pluripotent stem cells (hipsc) derived RPE cells transplanted on suitable membranes. Here, we focus on the surface modification of a porous membrane by atmospheric pressure plasma coating to enhance the adhesion of the RPE starting layer.